2017
DOI: 10.1002/ijc.31173
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: YY1 suppresses proliferation and migration of pancreatic ductal adenocarcinoma by regulating the CDKN3/MdM2/P53/P21 signaling pathway

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the malignant lethal tumors. It has been reported that the transcriptional regulator Yin Yang-1 (YY1) suppressed the invasion and metastasis of PDAC. However, the function of YY1 on proliferation and migration of pancreatic cancer remains to be clarified. In this study, we found that YY1 overexpression or knockdown can inhibit or promote the proliferation and migration of pancreatic cancer cells. Digital gene expression sequencing indicates that cyclin-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 43 publications
5
43
1
Order By: Relevance
“…However, previous studies have reported contradictory effects of CDKN3 on the cell cycle. Some studies have shown that CDKN3 acts as a cancer-promoting gene in a variety of ways to regulate the G1/S phase transition [40,41], while others have reported that CDKN3 plays an anti-tumour role via dephosphorylation of CDK2, thereby inhibiting the G1/S phase transition [31]. Therefore, the specific regulatory mechanism by which CDKN3 influences the cell cycle remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have reported contradictory effects of CDKN3 on the cell cycle. Some studies have shown that CDKN3 acts as a cancer-promoting gene in a variety of ways to regulate the G1/S phase transition [40,41], while others have reported that CDKN3 plays an anti-tumour role via dephosphorylation of CDK2, thereby inhibiting the G1/S phase transition [31]. Therefore, the specific regulatory mechanism by which CDKN3 influences the cell cycle remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that YY1 is overexpressed and serves as oncogene in numerous tumor types, including breast, ovary, colon, prostate, gastric and laryngeal cancer (17)(18)(19)(20)(21). However, YY1 may serve an inhibitory role in pancreatic cancer (22). A recent study demonstrated that the expression of YY1 was significantly upregulated in differentiated thyroid and anaplastic cancer (23).…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, Numb or p53 knockdown reversed the upregulation of wtp53 induced by silencing SRPK2 in response to oxaliplatin. p53 knockdown reversed the decrease in cell migration and invasion induced by SRPK2 silencing after treatment with oxaliplatin It is well known that p53 acts as a critical regulator in the malignant biology of various cancers [25,26]. Thus, we investigated whether SRPK2 promoted cell migration and invasion in a p53-dependent manner in PC cells.…”
Section: Srpk2 Regulated Cell Migration Invasion and Chemosensitivitmentioning
confidence: 96%